Adrift [movie tie-in] eaudiobook A true story of love, loss, and survival at sea. - Oldham Ashcraft, Tami (2018)
The heart-stopping memoir, soon to be a major motion picture starring Shailene Woodley and Sam Claflin, and directed by Baltasar Kormákur (Everest). Young and in love, their lives ahead of them, Tami Oldham and her fiancé Richard Sharp set sail from Tahiti under brilliant blue skies, with Tami's hometown of San Diego as their ultimate destination. But the two free spirits and avid sailors couldn't anticipate that less than two weeks into their voyage, they would sail directly into one of the most catastrophic hurricanes in recorded history. They found themselves battling pounding rain, waves the size of skyscrapers, and 140 knot winds. Richard tethered himself to the boat and sent Tami below to safety, and then all went eerily quiet. Hours later, Tami awakened to find the boat in ruins, and Richard nowhere in sight. Adrift is the story of Tami's miraculous forty-one-day journey to safety on a ravaged boat with no motor and no masts, and with little hope for rescue. It's a tale of love and survival on the high seas— an unforgettable story about resilience of the human spirit, and the transcendent power of love.